Aplicação de ferramentas do lean manufacturing para a obtenção de melhoria no indicador Overall Equipment Effectiveness (OEE) no setor de pintura de uma indústria automotiva - Nasr, Elias Ricardo (2021)
To meet market demands, companies are increasingly seeking continuous improvements in their processes and procedures. Some indicators help in the development of the company, where they contribute to find the problems that hinder the development and even the accomplishment of the tasks. One such indicator is the Overall Equipment Effectiveness (OEE) that works simultaneously with the availability, performance and quality of what is produced. In this way, the OEE allows us to find the main failures of a given sector, in a quantitative way, and thus to elaborate the best strategy to combat such failures. The objective of this work was to analyze the data provided by the OEE indicator after three months of applying layout improvements in a painting sector of the automotive company. For this, Lean Manufacturing was using tools such as Ishikawa Diagram, study of the Pareto Graph and the A3 tool. With the reorganization of the layout, a movement release was obtained due to the 23% movement space. There was an improvement in OEE in Machine A of 0.79%, Machine B of 11.47%, Machine C of 9.31% and Sealing of 8.35%. Thus, an increase in the sector's average OEE indicator by 7.48%, with the painting sector's OEE increasing to 77.5%.